A handbook for DNA-encoded chemistry : theory and applications for exploring chemical space and drug discovery - Goodnow, Robert A., Jr.; Wiley eBooks (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
This book comprehensively describes the development and practice of DNA-encoded library synthesis technology. Together, the chapters detail an approach to drug discovery that offers an attractive addition to the portfolio of existing hit generation technologies such as high-throughput screening, structure-based drug discovery and fragment-based screening. The book: Provides a valuable guide for understanding and applying DNA-encoded combinatorial chemistry Helps chemists generate and screen novel chemical libraries of large size and quality Bridges interdisciplinary areas of DNA-encoded combi.
Just enough knowledge? -- A brief history of the development of combinatorial chemistry and the emerging need for DNA-encoded chemistry -- A history of DNA-encoding -- DNA-compatible chemistry -- Foundations of a DNA-encoded library (DEL) -- Practices for synthesizing DNA-encoded libraries -- Chemical gene design for DNA-encoded libraries -- Analytical challenges for DNA-encoded library systems -- Information technology: functionality and architectures for DNA-encoding -- Theoretical considerations of the application of DNA-encoded libraries to drug discovery -- Begin with the end in mind : the hit-to-lead process -- Enumeration and visualization of large combinatorial chemical libraries -- Screening large compound collections -- Reported applications of DNA-encoded library chemistry -- Dual-pharmacophore DNA-encoded chemical libraries -- Hit identification and hit follow-up -- Using DNA to program chemical synthesis, discover new reactions, and detect ligand binding -- An outlook and the changing feasibility and economics of chemical diversity exploration with DNA-encoded combinatorial approaches -- Keeping the promise? an outlook on dna chemical library technology.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Combinatorial chemistry -- Technique; DNA -- Synthesis; MEDICAL -- Pharmacology; Combinatorial Chemistry Techniques -- methods; Drug Discovery -- methods; Gene Library; Small Molecule Libraries -- chemical synthesis; Electronic books